Application of quinpirole in the paraventricular thalamus facilitates emergence from isoflurane anesthesia in mice - Yawen Ao (Brain and Behavior, 2021)
Abstract Background and Purpose Dopamine is well‐known to contribute to emergence from anesthesia. Previous studies have demonstrated that the paraventricular thalamus (PVT) in the midline nuclei is crucial for wakefulness. Moreover, the PVT receives dopaminergic projections from the brainstem. Therefore, we hypothesize that the dopaminergic signaling in the PVT plays a role in emergence from isoflurane anesthesia. Methods We used c‐Fos immunohistochemistry to reveal the activity of PVT neurons in three groups: The first group (iso+EM‐) underwent the anesthesia protocol and was sacrificed before emergence. The second group (iso+EM+) underwent passive emergence from the same anesthesia protocol. The last group (oxy+) received oxygen. D2‐like agonist quinpirole (2 or 4 mM) or D2‐like antagonist raclopride (2 or 5 mM) was microinjected into the PVT, and their effects on emergence and induction time were analyzed. Surface cortical electroencephalogram (EEG) recordings were used to explore the effects of quinpirole injection into the PVT on cortical excitability during isoflurane anesthesia. The activity of PVT neurons after quinpirole injection was assessed by c‐Fos immunohistochemistry. Results The number of c‐Fos‐positive nuclei for the iso+EM+ group was significantly higher than the oxy+ and iso+EM‐ groups. Application of quinpirole (4 mM) into the PVT shortened emergence time compared with the saline group (p < .01). In contrast, administration of raclopride (2 mM) delayed emergence time (p < .05). Neither quinpirole nor raclopride exerted an effect on induction time. EEG analyses showed that quinpirole (4 mM) decreased the burst suppression ratio during isoflurane anesthesia (p < .01). The number of c‐Fos‐positive nuclei for the quinpirole (4 mM) group was significantly higher than saline group (p < .01). Conclusions Our findings suggest that the activity of PVT neurons is enhanced after emergence from anesthesia, and the dopaminergic signaling in the PVT may facilitate emergence from isoflurane anesthesia.